Legal Protection For Customers As Consumers Of Motor Vehicle Insurance Services (Decision Study Number: 24 PK / PDT / 2017) - Pangesti, Hayuning Dyah; Ratnawaty, Latifah; Mustika, Desty Anggie (Universitas Ibn Khaldun Bogor, 2024)
Consumers of motor vehicle insurance services are entitled to legal protection under Decision Study Number 24 PK / PDT / 2017. Pangesti Hayuning Dyah NPM 191103011027. In the case that an insurance claim is denied by the insurance company without a good reason, the insured person's legal protection is crucial. This is done to make sure the insurance firm fulfills all of its responsibilities to protect the insured's rights. regarding the procedure for settling insurance claims. In light of the history mentioned above, there are various ways to formulate the problem, specifically: 1) Motor vehicle insurance policies that provide consumer protection. 2) the insurance company's form of liability under Decision Number 24 PK / PDT / 2017 for insurance claims. Normative legal research is the kind of research methodology to be used in order to address the problem formulation. The study's findings include consumer protection policies for auto insurance that are based on the Insurance Law, the Civil Code, and the PK Law. According to decision number 24 PK / Pdt / 2017, the form of insurance liability for motor vehicle insurance claims is, in the meantime, compensating the defendant in accordance with the filed insurance claim